Enhancing knowledge sharing in high-tech firms: The moderating role of collectivism and power distance. Issue 3 (6th November 2017) - Chiu, Chou-Kang; Lin, Chieh-Peng; Tsai, Yuan-Hui; Teh, Siew-Fong
Abstract : Purpose: The purpose of this paper is to explore the development of knowledge sharing from the perspectives of broaden-and-build theory and expectancy theory. Its research purpose is to understand how knowledge sharing is driven by such predictors as optimism, pessimism, and positive affect through their complex interactions with collectivism or power distance. In the proposed model of this study, knowledge sharing relates to optimism and pessimism via the partial mediation of positive affect. At the same time, the influence of optimism, pessimism, and positive affect on knowledge sharing are moderated by the national culture of collectivism and power distance, respectively. Design/methodology/approach: This study's hypotheses were empirically tested using data from high-tech firms across Taiwan and Malaysia. Of the 550 questionnaires provided to the research participants, 397 usable questionnaires were collected (total response rate of 72.18 percent), with 237 usable questionnaires from Taiwanese employees and 160 usable questionnaires from Malaysian employees. The data from Taiwan and Malaysia were pooled and analyzed using: confirmatory factor analysis for verifying data validity, independent sample t -tests for verifying the consistency with previous literature regarding cultural differences, and hierarchical regression analysis for testing relational and moderating effects. Findings: This study demonstrates the integrated application of the broaden-and-build theory and expectancy theory for understanding optimism, pessimism, and positive affect in the development of knowledge sharing. The test results confirm that positive affect partially mediates the relationship between optimism and knowledge sharing and fully mediates the relationship between pessimism and knowledge sharing. Moreover, collectivism and power distance have significant moderating effects on most of the model paths between knowledge sharing and its predictors except for the relationship between pessimism and knowledge sharing. Originality/value: This study extends the expectancy theory to justify how optimistic and pessimistic expectations are stable traits that dominate the way employees share their knowledge sharing. This study shows how collectivism and power distance of Hofstede's cultural framework can be blended with the broaden-and-build theory and expectancy theory to jointly explain knowledge sharing. Besides, this study provides additional support to the adaptation theory of well-being that suggests psychosocial interventions, which manage to enhance well-being by leveraging positive affect, hold the promise of reducing stressful symptoms and boosting psychological resources among employees.